2018
DOI: 10.1080/23802359.2017.1422412
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial genome ofTesseropora rosea: molecular evidence for non-monophyly of the genusTetraclita

Abstract: The complete mitochondrial genome of Tesseropora rosea (Tetraclitidae) was presented. The genome is a circular molecule of 15,330 bp, which encodes 13 PCGs, two rRNA genes, and 22 tRNA genes. The length of all non-coding regions is 768 bp, with the longest one speculated as the control region (255 bp), which is located between 12S rRNA and trnK. Phylogenetic analysis based on mitochondrial PCGs shows that T. rosea is nested within the genus Tetraclita, more closely related to Tetraclita japonica than to Tetrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
5
5
0
Order By: Relevance
“…Song et al (2017) compared genome of four species from family Tetraclitidae, and found the mitochondrial gene order was highly conserved in the family. However, it has been reported that the genus Tetraclita does not constitute a monophyletic assemblage (Cai et al 2018); and Tetraclitidae is not monophyletic (Tsang et al 2015). Our result is consistent with these previous reports.…”
supporting
confidence: 93%
See 3 more Smart Citations
“…Song et al (2017) compared genome of four species from family Tetraclitidae, and found the mitochondrial gene order was highly conserved in the family. However, it has been reported that the genus Tetraclita does not constitute a monophyletic assemblage (Cai et al 2018); and Tetraclitidae is not monophyletic (Tsang et al 2015). Our result is consistent with these previous reports.…”
supporting
confidence: 93%
“…Result shows that T. squamosa squamosa is clustered with T. serrata into a branch (BP ¼ 100), and the two group with T. rosea and T. japonica, with T. rufotincta and T. divisa as the most distantly related species (Figure 1). In the tree, T. divisa as the most distantly related species within Tetraclitidae, which was consistent with the previous results (Song et al 2017;Cai et al 2018). Chelonbia testudinaria (Coronulidae) clusters with species from Tetraclitidae, which is consistent with Song et al (2017).…”
supporting
confidence: 91%
See 2 more Smart Citations
“…In the phylogenetic tree, M. tintinnabulum clustered with M. ajax into a branch (BP ¼ 100), and they grouped with M. volcano with high support (BP ¼ 100). Amphibalanus amphitrite as the most distantly related species within Balanidae, which was consistent with the previous results (Song et al 2017;Cai et al 2018). Besides, Austrobalanidae is nested within Tetraclitidae, and two families (Balanidae and Archaeobalanidae) are revealed non-monophyletic.…”
supporting
confidence: 92%